Safety Assessment of Ocean Current in Pantar Strait for Marine Tourism - Prasetyo, Akhmad Tri; Patriadi, Andi; Ahsin, Awaludin; Nurhidayat, Nurhidayat; Purwanto, Budi; Sobaruddin, Dyan Primana; Muslim, Muslim; Hendri, Muhammad; Hermialingga, Septi; Kurniasih, Eka Maya (Marine Science Department Diponegoro University, 2024)
The Pantar Strait with its coral reef ecosystem has encouraged many tourists to dive since the last decade. At least, ten coral reef ecosystem sites in Pantar Strait have been indicated as having potential for marine tourism, such as Munaseli Beach, Obisinga Beach, Umangdang Beach, Alor Eco Dive Resort, Ternate Island, Bakalang Beach, Pura Diving Spot, Nuhakepa Diving Spot, Pasir Putih Beach, and Savu Alor. This study illustrated the annual dynamics of ocean currents in Pantar Strait, subsequently assessing the safety rate of commercial diving at those tourism sites in each season. A three-dimensional hydrodynamic model was generated by the Delft3d flow module to illustrate the annual ocean current dynamic in the Pantar Strait. The safety assessment for marine tourism was classified into 3 levels (safe, alert, and dangerous). Ocean currents exceed maximum velocities in the west season. Various marine tourism sites close to steep slopes were not recommended for commercial diving. They are Munaseli Beach, Obisinga Beach, Pura Diving Spot, and Pasir Putih Beach. These sites experienced an increase in average currents that exceeded the safe threshold each season. Alor Eco Dive Resort was designated as the safest marine tourism, which showed a safe level for either average or maximum ocean currents in each season. Nuhakepa Diving Spot was designated as the second safest marine tourism. Several tourist sites that showed the danger of commercial diving in the west season were Umangdang Beach and Savu Alor. Many tourism sites showed an alert current for commercial diving in Springtide. Therefore, tourists are advised to avoid diving during the spring tide.